Studi Komparatif : Perbandingan Pengelolaan Rekam Medis pada Rumah Sakit di Hospital Sultan Abdul Aziz Shah Malaysia dan RSUD Cilacap - Nicky Putri Karla Dwi Amti; Yektiningtyastuti Yektiningtyastuti; Arum Astika Sari; Norizanne Binti Abd Rahim; Riskrisna Adi Pratama (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Medical record management is a crucial component of hospital service systems because it ensures continuity of care, information security and the improvement of healthcare service quality. The advancement of digitalization has encouraged hospitals to transition from manual systems to electronic medical records. However, the implementation varies across institutions and countries. This study aims to compare medical record management at Hospital Sultan Abdul Aziz Shah Malaysia and RSUD Cilacap Indonesia, based on six aspects: unit structure, management system, quality standards, regulatory framework, borrowing and returning mechanisms and the level of digitalization. This study employed a qualitative methodology with a comparative descriptive design. Data were collected through direct observation, documentation review including standard operating procedures (SOP) and flowcharts, as well as literature and regulatory analysis. The data were analyzed using qualitative comparative analysis through data reduction, data presentation in narrative form and comparative tables, and source triangulation. The findings indicate differences across the six examined aspects. Hospital Sultan Abdul Aziz Shah Malaysia has a specialized medical record unit and refers to ISO 9001:2015 and internal policies, while RSUD Cilacap integrates medical record management with clinical services and insurance claims, referring to Permenkes No.24/2022 and LARS DHP 2022 accreditation standards. Both hospitals implement a hybrid system combining manual and electronic records, although the scope of digitalization and document control system differs. These differences indicate that regulatory frameworks, organizational structures, and digital readiness influence medical record management practices and their implications for hospital service quality. Keywords: Comparison, Digitization, Electronic Medical Record, Medical Record Management, Service Quality.  ABSTRAK Pengelolaan rekam medis merupakan komponen penting dalam sistem pelayanan rumah sakit karena berperan dalam menjamin kesinambungan pelayanan, keamanan informasi dan peningkatan mutu layanan kesehatan. Perkembangan digitalisasi mendorong rumah sakit beralih dari sistem manual menuju rekam medis elektronik, namun implementasinya menunjukkan variasi antar institusi dan negara.Penelitian ini bertujuan membandingkan pengelolaan rekam medis di Hospital Sultan Abdul Aziz Shah Malaysia dan RSUD Cilacap Indonesia berdasarkan enam aspek yaitu struktur unit, sistem pengelolaan, standar mutu, regulasi, mekanisme, peminjaman dan pengembalian, serta tingkat digitalisasi. Penelitian ini menggunakan metodologi kualitatif dengan desain deskripsi komparatif. Data dikumpulkan melalui observasi langsung, studi dokumentasi (SPO/Flowchart) serta telaah literatur dan regulasi, kemudian dianalisis melalui reduksi data, penyajian data dalam bentuk narasi dan tabel perbandingan, serta triangulasi sumber. Hasil Penelitian menunjukkan adanya perbedaan pada enam aspek yaitu Hospital Sultan Abdul Aziz Shah Malaysia memiliki unit rekam medis terspesialisasi dan mengacu pada ISO 9001:2015 serta kebijakan internal, sedangkan RSUD Cilacap terintegrasi dengan layanan dan klaim, beracuan Permenkes 24/2022 dan LARS DHP 2022. Keduanya menerapkan sistem hybrid, namun cakupan digitalisasi dan sistem kontrol berkas berbeda. Perbedaan tersebut menunjukkan bahwa konteks regulasi, organisasi dan kesiapan digital memengaruhi praktik pengelolaan rekam medis serta implikasinya terhadap mutu pelayanan rumah sakit. Kata Kunci: Digitalisasi, Mutu Pelayanan, Pengelolaan Rekam Medis, Perbandingan, Rekam Medis Elektronik.